P Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Kelas III SD Negeri Sawah Besar 01 Semester Genap 2022/2023 - Rina Susanti, Desy Riani Hafshah (Jurnal Kualita Pendidikan, 2023)
DESY RIANI HAFSHAH."The Influence of Problem-Based Learning Models on Learning Outcomes of Class III Students of SD Negeri Sawah Besar 01 Even Semester Year 2022/2023". The background that drives this research is SDN Sawah Besar 01 which uses a conventional learning model which makes learning outcomes not optimal so it requires a learning model that can increase student interest and learning outcomes. The formulation of the problem of this research is whether the learning model is Problem Based Learning ( PBL) affects the learning outcomes of class III students at SD Negeri Sawah Besar 01 even semester in 2022/2023?. This type of research is quantitative research in the form of a Quasi Experiment with the Nonequivalent Control Group Design form. The population in this study were class III students at SDN Sawah Besar 01 Semarang. The samples taken were 50 students, of which 25 students were in the experimental class and 25 were in the control class. The data in this study were obtained from tests, observations and documentation. Based on the results of data analysis in the control class, the average pretest score was 72.67 and the posttest average value was 75.84. In the experimental class, the average pretest score was 78.24 and the posttest average value was 84.16. The results of the hypothesis test obtained a significant value of 0.047 <probability of 0.05 which indicates is rejected and is accepted, meaning that there is an influence on learning outcomes using the Problem Based Learning model for class III students at SDN Sawah Besar 01 Semester Even.